Cognitive behavioural therapy for chronic fatigue and chronic fatigue syndrome: outcomes from a specialist clinic in the UK. (October 2020) - Adamson, James; Ali, Sheila; Santhouse, Alastair; Wessely, Simon; Chalder, Trudie
Objectives: Cognitive behavioural therapy is commonly used to treat chronic fatigue syndrome and has been shown to be effective for reducing fatigue and improving physical functioning. Most of the evidence on the effectiveness of cognitive behavioural therapy for chronic fatigue syndrome is from randomised control trials, but there are only a few studies in naturalistic treatment settings. Our aim was to examine the effectiveness of cognitive behavioural therapy for chronic fatigue syndrome in a naturalistic setting and examine what factors, if any, predicted outcome. Design: Using linear mixed effects analysis, we analysed patients' self-reported symptomology over the course of treatment and at three-month follow-up. Furthermore, we explored what baseline factors were associated with improvement at follow-up. Setting: Data were available for 995 patients receiving cognitive behavioural therapy for chronic fatigue syndrome at an outpatient clinic in the UK. Participants: Participants were referred consecutively to a specialist unit for chronic fatigue or chronic fatigue syndrome. Main outcome measures: Patients were assessed throughout their treatment using self-report measures including the Chalder Fatigue Scale, 36-item Short Form Health Survey, Hospital Anxiety and Depression Scale and Global Improvement and Satisfaction. Results: Patients' fatigue, physical functioning and social adjustment scores significantly improved over the duration of treatment with medium to large effect sizes (|d| = 0.45–0.91). Furthermore, 85% of patients self-reported that they felt an improvement in their fatigue at follow-up and 90% were satisfied with their treatment. None of the regression models convincingly predicted improvement in outcomes with the best model being (R 2 = 0.137). Conclusions: Patients' fatigue, physical functioning and social adjustment all significantly improved following cognitive behavioural therapy for chronic fatigue syndrome in a naturalistic outpatient setting. These findings support the growing evidence from previous randomised control trials and suggest that cognitive behavioural therapy could be an effective treatment in routine treatment settings.